2013
DOI: 10.1177/193229681300700113
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Diabetes Self-Management: A Mixed-Methods Analysis of a Mobile Health Intervention for Inner-City Latino Patients

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…Decisionmaking skills were significantly associated with self-efficacy, which is in line with the findings of previous studies (Kuo et al 2014). The lack of a significant association between diet knowledge and self-efficacy, however, was not surprising, because similar results have been reported (Burner et al 2013;Jung et al 2015). The majority of the participants in this study suffered from mid-and long-term diabetes and diet knowledge has been linked to feelings of deprivation and restriction in such patients.…”
Section: Discussionsupporting
confidence: 91%
“…Decisionmaking skills were significantly associated with self-efficacy, which is in line with the findings of previous studies (Kuo et al 2014). The lack of a significant association between diet knowledge and self-efficacy, however, was not surprising, because similar results have been reported (Burner et al 2013;Jung et al 2015). The majority of the participants in this study suffered from mid-and long-term diabetes and diet knowledge has been linked to feelings of deprivation and restriction in such patients.…”
Section: Discussionsupporting
confidence: 91%
“…Text messages delivered via mobile or smartphone continue to be a common strategy for DSM, either alone48,49 or in combination with other technologies 50. Recent studies conducted in T2DM4850 and T1DM49 evaluated the impact of text messages and demonstrated overall improvements in diet and level of exercise,50 increasing weekly exercise and daily consumption of fruits and vegetables,48,49 lowering fat consumption,49 and enhancing skills in food label reading 48.…”
Section: Ehealth Technologies To Support Diet and Physical Activity Imentioning
confidence: 99%
“…1 University of South Florida, Tampa, FL, USA inflexible work hours, lack of knowledge regarding food preparation, and fatigue and other somatic complaints related to occupational stresses (Burner et al, 2013;Cherrington, Ayala, Scarinci, & Corbie-Smith, 2011).…”
Section: Research-article2015mentioning
confidence: 99%
“…According to the most recent U.S. Census data, Hispanics accounted for 16% of the U.S. population (50.5 million people) in 2010, up from 13% (35.3 million people) in 2000 (U.S. Census Bureau, 2010). As research on health disparities and inequalities grows (Centers for Disease Control and Prevention [CDC], 2010), it has become apparent that Hispanic Americans face a distinct set of health challenges, including disproportionately higher health risks, decreased access to health services, reduced likelihood of receiving needed health care, and lower quality of care as compared to non-Hispanic Whites (Burner, Menchine, Taylor, & Arora, 2013;Caballero, 2005;Elder et al, 2006;Gary, Narayan, Gregg, Beckles, & Saaddine, 2003;Lorig, Ritter, & Gonzalez, 2003;Munoz & Mendelson, 2005). These health needs demand increased research regarding avenues for addressing disparities among Hispanic Americans.…”
Section: Introductionmentioning
confidence: 99%